Threat of landslides hazard at the core zone of Cultural Conservation Strategic Area of Gunung Padang megalithic site, in Cianjur District - Indarti Komala Dewi; Ruslan Fauzi; M. Yogie Syahbandar (Universitas Pakuan, 2022)
The megalithic site of Gunung Padang is an area prone to landslides. Based on the Regulation of Cianjur District No. 17 of 2012, this site area is designated as a Cultural Conservation Strategic Area. This study aims to analyze the potential for landslide hazards in the Gunung Padang Megalithic Site area. The research method is quantitative. Primary data was collected through observation and interview experts; secondary data was collected through literature studies and agency surveys. The analytical method used is quantitative through analysis of Geographic Information Systems (GIS), with overlay and weighting techniques. The results showed three landslide susceptibility classifications: very high, medium, and very low. A very high level of landslide hazard is found in the area around the site, which is currently exposed, amounting to 9.03% of the core zone of the Cultural Conservation Strategic Area.Situs megalitikum Gunung Padang merupakan kawasan rawan longsor. Berdasarkan Peraturan Bupati Cianjur No. 17 Tahun 2012, kawasan situs ini ditetapkan sebagai Kawasan Strategis Cagar Budaya. Penelitian ini bertujuan untuk menganalisis potensi bahaya longsor di kawasan Situs Megalitikum Gunung Padang. Metode penelitian adalah kuantitatif. Data primer dikumpulkan melalui observasi dan wawancara ahli, data sekunder dikumpulkan melalui studi literatur dan survei keagenan. Metode analisis yang digunakan adalah kuantitatif melalui analisis Sistem Informasi Geografis (SIG), dengan teknik overlay dan pembobotan. Hasil penelitian menunjukkan tiga klasifikasi kerawanan longsor yaitu sangat tinggi, sedang dan sangat sangat rendah. Tingkat kerawanan longsor yang sangat tinggi terdapat di wilayah sekitar tapak yang saat ini terpapar, yaitu sebesar 9,03% dari zona inti kawasan strategis cagar budaya.